A new species of the subterranean genus Stygobromus (Amphipoda: Crangonyctidae) from a cave spring in northern Florida, USA - Holsinger, John R.; Sawicki, Thomas R. (Zootaxa, 2016)
A relatively large, distinct new species of the subterranean amphipod crustacean genus Stygobromus (Amphipoda: Crangonyctidae) measuring 13 mm in length is described from Skipper Spring, a cave spring in the northwestern “panhandle” of Florida, USA. This is the first species of the genus described from the state of Florida where it is described from only 3 females. A fourth much smaller specimen of this species was collected from nearby Miller’s Crossing Spring on Holmes Creek. All other stygomorphic amphipod species recorded from the state of Florida have been in the genus Crangonyx.